PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT MAKMUR UTAMA RAYA - Diana, Diana; Suhardi, Suhardi (SCIENTIA JOURNAL, 2019)
In this globalization, economic competition between companies is becoming increasingly strict both domestically and globally, competing with each other. Companies are required to always improve and maintain the quality and performance of employees to be effective and efficient and able to compete with other companies. These research purpose for examine whether the company’s work motivation, work discipline and leadership style possess an influence on employe performance at PT Makmur Utama Raya. Employees of PT Makmur Utama Raya in june 2018 as much 118 respondent, is the population of this study. Sampling technique uses saturated sampling, the total sample in this study are 118 respondent. The countimg up activity apply SPSS version 21.0 software. Multiple linear regression analysis is the method that used to analysis data in this study. The result shows that employe performance is have an impact on with some element. Those are work motivation, leadership style and work discipline. The number of 0,659 (65,9%) represents the R Square Value. It means the work motivation, leadership style and work discipline have effected the employee performance (Y) for 65,9%, rest of 34,1% is effected by other variable out of this research.